고강도강 맞대기 용접 시험편의 루트갭 변경에 따른 피로강도 평가 - 김호정(Ho-Jung Kim); 강성원(Sung-Won Kang); 김명현(Myung-Hyun Kim) (大韓造船學會 論文集, 2011)
In this study, a series of fatigue tests was conducted to evaluate fatigue strength for the root gap difference with high strength steel with butt welded joints. A finite element analysis using effective notch stress method was also performed to compare effective notch factors each other with butt welded specimens made by copper backing. The results of fatigue tests were classified according to the root gap difference. Fatigue life of butt welded specimens is presented for determining the root gap of high strength steel with butt welded joints in terms of fatigue strength. Then effective notch stress was applied to interpret fatigue strength of butt welded specimen model which is reflected actual measured dimensions. As a result, fatigue strength of high strength steel with butt welded specimens is increased by root gap gets longer in length.